2019
DOI: 10.5194/amt-12-5201-2019
|View full text |Cite
|
Sign up to set email alerts
|

Cross-evaluation of GEMS tropospheric ozone retrieval performance using OMI data and the use of an ozonesonde dataset over East Asia for validation

Abstract: Abstract. The Geostationary Environment Monitoring Spectrometer (GEMS) is scheduled to be launched in 2019–2020 on board the GEO-KOMPSAT (GEOstationary KOrea Multi-Purpose SATellite)-2B, contributing as the Asian partner of the global geostationary constellation of air quality monitoring. To support this air quality satellite mission, we perform a cross-evaluation of simulated GEMS ozone profile retrievals from OMI (Ozone Monitoring Instrument) data based on the optimal estimation and ozonesonde measurements w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Previous literature focusing on ozonesonde trends has often focused on specific regions or individual sonde launch locations. In many applications, ozonesonde information is used to validate or assess satellite retrievals rather than as a primary source to investigate trends (Boynard et al, 2018;Shi et al, 2017;Hulswar et al, 2020;Huang et al, 2017;Bak et al, 2019). To date, the most extensive look at ozonesonde trends over Europe is provided by Logan et al (2012), where trends up to 2011 were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature focusing on ozonesonde trends has often focused on specific regions or individual sonde launch locations. In many applications, ozonesonde information is used to validate or assess satellite retrievals rather than as a primary source to investigate trends (Boynard et al, 2018;Shi et al, 2017;Hulswar et al, 2020;Huang et al, 2017;Bak et al, 2019). To date, the most extensive look at ozonesonde trends over Europe is provided by Logan et al (2012), where trends up to 2011 were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Ozonesonde measurements are reported in units of partial pressure (mPa) with vertical resolution of about 100 m by the Korea Meteorological Administration (KMA). Bak et al (2019) demonstrated that Pohang ozonesonde measurements are a stable set of reference profiles for validating satellite products, with quality comparable to ECC ozonesonde measurements in Japan and Hong Kong. To improve the data quality, we screened out sounding measurements at balloon burst altitudes higher than 200 hPa and observations of either tropospheric ozone column values above 80 DU or stratospheric ozone column values below 100 DU.…”
Section: Ozonesonde Measurementsmentioning
confidence: 86%
“…During the IOT, Defect 3 caused spatial discontinuity to the retrieved cloud and AEH distribution, which made the fitting window of the products modified to avoid bad pixel effects. Ozone properties are also affected by Defect 2 (300-400 nm) as the spectral radiances within 300-380 nm are the major information for the retrieval of GEMS (Bak et al, 2019).…”
Section: Bad Pixelmentioning
confidence: 99%